2011
DOI: 10.1128/jvi.02174-10
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the Black-Tailed Prairie Dog (Cynomys ludovicianus) as a Novel Animal Model for Comparing Smallpox Vaccines Administered Preexposure in both High- and Low-Dose Monkeypox Virus Challenges

Abstract: The 2003 monkeypox virus (MPXV) outbreak and subsequent laboratory studies demonstrated that the black-tailed prairie dog is susceptible to MPXV infection and that the ensuing rash illness is similar to human systemic orthopoxvirus (OPXV) infection, including a 7-to 9-day incubation period and, likely, in some cases a respiratory route of infection; these features distinguish this model from others. The need for safe and efficacious vaccines for OPVX in areas where it is endemic or epidemic is important to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 76 publications
1
47
0
Order By: Relevance
“…Monkeypox virus infection of prairie dogs produces disease that is highly similar to that in humans after systemic OPV infection, and protection from disease occurs when animals are vaccinated prior to challenge with monkeypox virus (24,25). Additionally, since vaccination in humans produces an antibody response correlated with protection, a highly similar response in prairie dogs would further support their use as a surrogate animal model of OPV vaccination.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Monkeypox virus infection of prairie dogs produces disease that is highly similar to that in humans after systemic OPV infection, and protection from disease occurs when animals are vaccinated prior to challenge with monkeypox virus (24,25). Additionally, since vaccination in humans produces an antibody response correlated with protection, a highly similar response in prairie dogs would further support their use as a surrogate animal model of OPV vaccination.…”
Section: Discussionmentioning
confidence: 84%
“…In Dryvax revaccination cases, only a modest increase in the number of recognized targets has been seen (40). We also recently showed that disease severity, as judged by weight loss, lesion count, and nasal involvement, was significantly limited upon challenge after vaccination, particularly after Dryvax or Acam2000 vaccination (25). Although the limited number of immunodominant antigens after vaccination may have been expected to continue dominating the profile, along with the addition of a few novel targets that may have been recognized during vaccination but failed to generate a detectable antibody response, the large increase here suggests that differences in virus pathogenicities or life cycles affect immune recognition.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations